Experimental study of precast segmental columns with unbonded tendons under cyclic loading - Li, C.; Hao, Hong; Zhang, Xihong; Bi, Kaiming (Multi-Science Publishing, 2018)
© 2017, © The Author(s) 2017. Precast segmental column has attracted a lot of interests over the past decade. It has become more and more popular in construction industry to achieve fast construction, improve construction quality and reduce environmental impact. Many factors including the energy dissipation bar, number of segments, prestressing force and shear keys could affect the performance of segmental column, but each of previous studies normally focused on investigating one or two of these factors. Since different previous studies used different materials, different structural dimensions, different axial loads and different testing methods, it is difficult to have comprehensive comparisons of the influences of these parameters on the performances of segmental columns. Moreover, limited studies indicated that shear keys had insignificant influences on performances of segmental columns subjected to cyclic loadings, while other studies revealed shear keys contribute to resisting impact loads but could lead to more severe damage due to stress concentration. In this study, cyclic tests were carried out to systematically assess the performance of segmental columns. Special attentions were paid on the influences of shear keys on column responses. Five scaled segmental columns with different designs were tested to study their damage mode, hysteretic behaviour, residual drift and energy dissipation capacity. One monolithic column was also tested as a reference. Test results showed that comparing with the monolithic column, the segmental columns exhibited better ductility and smaller residual drift, indicating better seismic performance, but segmental columns had less loading capacity and absorbed less energy. The influences of different designs including energy dissipation bar between adjacent segments, number of segments, prestressing force level in the tendon and concrete shear key on the seismic performance of segmental column were investigated and discussed.